Integrating marketing communications - Kerlin, Annette (Henry Stewart Talks, 2008)
The evolution of marketing from customer relationship marketing to customer experience marketing, Overview of the changing needs of customers and the markets we operate in, New approach to integrated marketing and communications, Core themes and business drivers key to building and implementing a customer experience driven marketing strategy, Key headlines for delivering successful integrated marketing communications
Archived at 2022/03/17